A Review of Possible Health Consequences of Genetically Modified Foods - Yahaya, T.; Bunza, M.D.A.; Shehu, K. (Al-Hikmah Journal of Pure and Applied Sciences (AJPAS), 2017)
Many countries are considering the option of importing genetically modified (GM) foods to reduce food shortage. However,its planned introduction in Nigeria has been trailed with controversy due to its possible health consequences. This articlereviewed the possible health effects of GM foods to clear the controversy surrounding its introduction. The Google searchengine was used to retrieve information on the subject from reliable sources on the internet such as PubMed, Google Scholar,among others. Studies funded by various governments reported no safety issue with GM foods, while independentresearchers say GM foods can cause allergies, cancer, antibiotic resistance and toxicity. Some scientific studies implicatingGM foods in serious health consequences have appeared in reputable journals in the past, but were later withdrawn, allegedlydue to pressure from governments and companies. Policy makers in Nigeria are therefore advised to carry out short and longterm studies of possible health effects of GM foods and put in place palliative measures before introducing them.